Studi Literatur Pengembangan Instrumen Tes Literasi Ekonomi Berbasis Faktor Analisis dengan Teknik Meta Analisis - Selviani Selviani (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to determine the literacy of the Development of Economic Literacy Test Instruments Based on Factor Analysis with the Meta-Analysis Technique. The research methodology uses a systematic literature review on the development of an economic literacy test instrument based on factor analysis and its impact on students' critical thinking skills. PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) and Bibliometric analysis have been applied to answer research questions. The PRISMA method was used to shortlist and select the 2007-2021 works from Scopus and Google Scholar with explicit inclusion and exclusion criteria. The research results show that research results from 2007 to 2021 experienced a significant increase, especially in 2014 with a total of 4 journal publications. Conclusion regarding the development of economic literacy test instruments dominated by journal articles as much as 80% and seminars as much as 20%. The keywords regarding the development of economic literacy test instruments that are most often used by searchers are development, financial literacy, and validation.